The frequency and age presentation of G6PD Deficiency in 200 patients of Hemolytic anaemia - Khattak, Muhammad Ishaq; Ishaq, Tehniyat; Subhan, Muhammad; Afridi, Javed (Journal of Postgraduate Medical Institute, 2011)
To determine the frequency of G6PD deficiency in the etiology of anaemia and jaundice and to determine the most commona ge of presentation with anaemia and Jaundice due to G6PD deficiency in adults. We did a hospital based study in the department of medicine KTH, peshawar from June to December 2003. The data of adult patients with signs and symptoms of anaemia and jaundice wa collected on structured proforma. the clinical presentation and laboratory investigation results were documented. G6PD deficiency is not an uncommon cause of jaundice and anamia is our patient. The jaundice due to G6PD mainly affects the adults in 2nd or 3rd decade. Therefore, all the childrena dn adults with jaundice and anaemia should be screened for G6PD status.